Pengaruh Celebrity Endorser, Testimoni, Kualitas Pelayanan Terhadap Kepercayaan Konsumen di Instagram - Abetha Alma Rosaria; Yon Rizal; Pujiati Pujiati (Economic Education and Entrepreneurship Journal, 2020)
The Effect of Celebrity Endorser, Testimony, and Quality of Service To Consumer Trust in Instagram. This research aims to determine the effect of celebrity endorser, testimonials, and the service quality on consumer confidence in micro business on social media instagram of Economic Education's students in University of Lampung. The population of this research were all students of Economic Education in year of force 2016, 2017, 2018 and 2019, totaling 263students. The number of samples in this study amounted to 73 students using the nonprobability sampling method supported by purposive sampling. The results showed that there was an influence of celebrity endorsers, testimonials, and service quality on consumer confidence in micro business on social media Instagram of Economic Education's students in University of Lampung. This can be proven by calculating Fcount Ftable or 6.835 2.74 and the significance value (sig.) α= (0,05) or 0,000 0,05. The coefficient of determination gained 0.229 or 22.9% of consumer trust is influenced by celebrity endorsers, testimonials, and service quality, the remaining 77.1% is influenced by other factorsthat are not included in this research.Keywords: Celebrity Endorser, Consumer Trust, Quality of Service, Testimony http://dx.doi.org/10.23960/E3J/v3i2.pp51-58